Vascular Plants of Kshipra River Bank and its Tributaries, Madhya Pradesh, India - Tiwari, Arjun Prasad; Dubey, P. C.; Sikarwar, R. L. S.; Khanna, K. K. (Indian Forester, 2017)
The present study of the vascular plants of Kshipra river bank and its tributaries was carried out from 2014 to 2016. A total of 327 species under 241 genera belonging to 75 families of vascular plants were recorded. Out of these, 324 species are angiosperms belonging to 238 genera and 72 families, 3 species are pteridophytes belonging to 3 genera and 3 families. In angiosperms, dicotyledons comprised of 243 species under 178 genera and 60 families and the monocotyledons comprised of 81 species belonging to 60 genera and 12 families. Poaceae is the largest family (41 species) while Cyperus, Euphorbia, Ficus, Indigofera and Ipomoea are dominant genera (5 species each). The details of analysis of habit, status of plants and economic importance have been provided in the paper.